Arterial protection system failure: hemodynamic arteriosclerosis - Palma, Eduardo C (Cirugía del Uruguay, 2020)
1) A system of protection for arterial walls designed to prevent ihe traumatic action of the intra-arterial hemodynamic force, is described. When, owing to whatever circumstance, this artery-protection system ( A.P.S.) fails hemodynamic arteriosclerotic lesions are brough about. 2) A.P.S. in vol ves: a) fatty cellular envelopes which surround most of the economy arteries; b) in the hcart and major vessels, it is completed by pericardiac serous envelope and the intra-toracic negative pressure; c) in the arteries of the pulmonary system the negative pressure of the pulmonary parenchyma is the main protective component; d) the arteries of the central nervous system are immersed in C.S.F. wich in term makes up a means of parietal protection. 3) Hemodynamic arteriosclerosis is caused by several mechanims: a) contact of a hard tissue wi th the artery; b) immedia te contact of two arteries; c) in certain cases, in the areas of origin of the arterial branches which arise perpendicularly or at the arterial bends; d) owing to ischemia of the arterial walls, as a result of obliteration of the vasa-vasorum because of hemodynamic arteriosclerosis of these supplying vessels. 4) At surgery, A.P.S. 'hould be preserved so far as possible in order to prevent the evelopment of post-operntive arteriosclerotic lesions.